Case studies for the medical office : - Sanderson, Susan M. (McGraw-Hil, 2010)
This capstone simulation using Medisoft Patient Billing Software, Version 14, gives students enhanced training that fosters superior qualifications for a variety of medical office jobs. Extensive hands-on practice with realistic source documents teaches students to input information, schedule appointments, and handle billing, reports, and other essential tasks. The simulation is recommended for students who have completed the study of Medisoft Advanced Version 14 using Computers in the Medical Office or Patient Billing.